2011
DOI: 10.1097/won.0b013e31822efc86
|View full text |Cite
|
Sign up to set email alerts
|

Post-thrombotic Syndrome Patient Education Based on the Health Belief Model

Abstract: Background and objective: Breast cancer is the most common cancer among women. One of the ways to decrease the death due to breast cancer is early detection through mammography. This study considered the impact of education based on Health Belief Model (HBM) on teachers using mammography in Bushehr. Materials and methods: The current study was a random clinical trial which included of 120 teachers over 40 years old. The teachers were randomly divided in two groups. The teachers of intervention group received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In line with previous studies, the main reason for noncompliance reported by the patients in the SOX trial was difficulty putting the stockings on 41‐43 . Similarly, in the IDEAL‐DVT (Individually Tailored Elastic Compression Therapy After Deep Venous Thrombosis in Relation to the Incidence of Post Thrombotic Syndrome) trial, the second most important determinant of good compliance, after PTS risk reduction, was the ability to put the ECS on independently 44 .…”
Section: Potential Limitations Of Published Rcts Assessing the Efficasupporting
confidence: 75%
“…In line with previous studies, the main reason for noncompliance reported by the patients in the SOX trial was difficulty putting the stockings on 41‐43 . Similarly, in the IDEAL‐DVT (Individually Tailored Elastic Compression Therapy After Deep Venous Thrombosis in Relation to the Incidence of Post Thrombotic Syndrome) trial, the second most important determinant of good compliance, after PTS risk reduction, was the ability to put the ECS on independently 44 .…”
Section: Potential Limitations Of Published Rcts Assessing the Efficasupporting
confidence: 75%
“…In the second study, 13 patients after DVT were asked to indicate whether they agreed or disagreed with some predefined statements on (among other things) barriers that prevented the use of an ECS. Patients mentioned that difficulty in the application of the ECS ( n = 8), discomfort of the ECS ( n = 4) and appearance of the ECS ( n = 4) prevented them from being compliant .…”
Section: Introductionmentioning
confidence: 99%
“…10 11 One of the reasons for non-compliance include difficulties putting ECS on and/or removing the ECS. [12][13][14][15][16] Some patients need assistive devices to preserve self-reliance, and a smaller proportion of patients rely on home care to assist with the application and removal of the ECS. The proportion of patients needing home care for this indication is not well known.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%